Penggunaan Bigdata Transportasi Berpotensi Meningkatkan Efisiensi Sistem Transportasi Kota - Nadhila Effendy; Andi Lukman M; Egy Andarwati Sulistyaning T.F; Tubagus Imam Panji Parawansa; Siti Badriyah Ningsih (Action Research Literate, 2023)
The use of Bigdata in urban transportation can provide significant benefits for users and governments. However, the use of Bigdata also has challenges that need to be addressed. In this article, the author discusses the results of Bigdata research in urban transportation, comparisons with previous research, established theories, and the implications and challenges of using Bigdata in urban transportation. Based on the research results and comparisons with previous research and established theories, the author concludes that the use of Bigdata in urban transportation can improve the efficiency of urban transportation systems, reduce congestion, improve transportation safety, and improve user comfort. However, the use of Bigdata also has challenges such as privacy issues, data security, and technology access gaps. Therefore, the author provides several suggestions for optimizing the use of Bigdata in urban transportation, including increasing cooperation between the government, private sector, and society, developing good privacy policies, improving technology accessibility, developing sustainable transportation systems, and increasing data literacy.